The great puppy invasion - Heim, Alastair; Smith, Kim, 1986- (Boston : Clarion Books, Houghton Mifflin Harcourt, 2017)
When Strictville, where fun, play, and cuteness are all forbidden, is invaded by hundreds of adorable puppies, everyone is terrified until Teddy decides to shake the littlest puppy's paw.
Kirkus Review, August 2017
2.2
K-3
K-3
Kirkus Review
AD520L
Keywords: Dogs -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; City and town life -- Juvenile fiction; Dogs -- Fiction; Animals -- Infancy -- Fiction; City and town life -- Fiction; Dogs -- Fiction; Animal babies -- Fiction; City and town life -- Fiction; Humorous fiction; Picture books